2000
DOI: 10.1093/emboj/19.23.6517
|View full text |Cite
|
Sign up to set email alerts
|

p53-inducible Wip1 phosphatase mediates a negative feedback regulation of p38 MAPK-p53 signaling in response to UV radiation

Abstract: The stress-responsive p38 MAPK, when activated by genotoxic stresses such as UV radiation, enhances p53 activity by phosphorylation and leads to cell cycle arrest or apoptosis. Here we report that a member of the protein phosphatase type 2C family, Wip1, has a role in down-regulating p38-p53 signaling during the recovery phase of the damaged cells. Wip1 was originally identi®ed as a gene whose expression is induced following g or UV radiation in a p53-dependent manner. We found that Wip1 is also inducible by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
404
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 403 publications
(424 citation statements)
references
References 45 publications
17
404
1
2
Order By: Relevance
“…To understand the potential reason for such a discrepancy, we analyzed the effect of MKK6 overexpression on the level of endogenous Wip1 in MMTV-MKK6 transgenics. It was previously shown that the MKK6/p38 MAPK-dependent signaling pathway could efficiently upregulate Wip1 expression (Takekawa et al, 2000). Analysis of Wip1 mRNA expression by real-time polymerase chain reaction (PCR) revealed that breast epithelia from MMTV-MKK6 females contained B2.5 more Wip1 mRNA compared to wild-type mice (Figure 2d).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…To understand the potential reason for such a discrepancy, we analyzed the effect of MKK6 overexpression on the level of endogenous Wip1 in MMTV-MKK6 transgenics. It was previously shown that the MKK6/p38 MAPK-dependent signaling pathway could efficiently upregulate Wip1 expression (Takekawa et al, 2000). Analysis of Wip1 mRNA expression by real-time polymerase chain reaction (PCR) revealed that breast epithelia from MMTV-MKK6 females contained B2.5 more Wip1 mRNA compared to wild-type mice (Figure 2d).…”
mentioning
confidence: 85%
“…Previous analysis showed that Wip1 could modulate apoptotic response and proliferation (Bulavin et al, 2004;Belova et al, 2005), which could explain the early onset of tumors observed in MMTV-ErbB2/ PPM1D mice. While there was no significant difference in the rate of apoptosis between analyzed samples Several potential downstream targets of Wip1 have been identified in vitro: p38 MAPK, p53, Chk1, Chk2 and ataxia-telangiectasia mutated (ATM) (Takekawa et al, 2000;Lu et al, 2005;Fujimoto et al, 2006;Shreeram et al, 2006). The role of p38 MAPK is particularly interesting, as we previously found that Wip1-deficient mice show a p38 MAPK-dependent delay in the onset of breast cancer when crossed with MMTV-ErbB2 transgenic mice (Bulavin et al, 2004).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Wip1 also dephosphorylates p38 and UNG2 at pT180GY and pT6LY sites, respectively (Takekawa et al, 2000;Lu et al, 2004). In the case of the p38 MAP kinase, the TGY motif is part of the activation loop of the kinase and is diphosphorylated on Thr and Tyr residues when p38 is activated.…”
Section: Wip1 Phosphatase Antagonizes Chk2 Activation M Oliva-trastoymentioning
confidence: 99%
“…In response to genotoxic stress, Wip1 was recently shown to downregulate several checkpoint pathways. First, Wip1 binds and dephosphorylates UV-activated p38 MAP kinase, inhibiting p38 activity and preventing p53 stabilization (Takekawa et al, 2000). Second, Wip1 dephosphorylates p53 at phospho-Ser15, which is targeted by the ATM/ATR kinases (Lu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%